2021
DOI: 10.4007/annals.2021.193.2.5
|View full text |Cite
|
Sign up to set email alerts
|

The spread of a finite group

Abstract: A group G is said to be 3 2 -generated if every nontrivial element belongs to a generating pair. It is easy to see that if G has this property then every proper quotient of G is cyclic. In this paper we prove that the converse is true for finite groups, which settles a conjecture of Breuer, Guralnick and Kantor from 2008. In fact, we prove a much stronger result, which solves a problem posed by Brenner and Wiegold in 1975. Namely, if G is a finite group and every proper quotient of G is cyclic, then for any pa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
48
0

Year Published

2021
2021
2022
2022

Publication Types

Select...
4
4

Relationship

1
7

Authors

Journals

citations
Cited by 30 publications
(49 citation statements)
references
References 54 publications
(206 reference statements)
0
48
0
Order By: Relevance
“…It is known that Γ + (G) is connected in several cases. For instance, Burness et al [11] showed that if G is a finite group such that every proper quotient of G is cyclic, then Γ(G) = Γ + (G) and Γ(G) is connected with diameter at most 2 (the special case where G is simple was proved by Guralnick and Kantor [21] and Breuer et al [3]).…”
Section: Comparison With Usual Generationmentioning
confidence: 99%
“…It is known that Γ + (G) is connected in several cases. For instance, Burness et al [11] showed that if G is a finite group such that every proper quotient of G is cyclic, then Γ(G) = Γ + (G) and Γ(G) is connected with diameter at most 2 (the special case where G is simple was proved by Guralnick and Kantor [21] and Breuer et al [3]).…”
Section: Comparison With Usual Generationmentioning
confidence: 99%
“…The only almost simple sporadic group whose maximal subgroups are not fully determined is M. The published results on maximal subgroups of M include complete classifications, except for the possibility of maximal subgroups with socle PSL 2 (8), PSL 2 (13), PSL 2 (16) and PSU 3 (4). Of these, PSL 2 (8) and PSL 2 (16) were considered in unpublished work of P. E. Holmes, and papers by Wilson on PSL 2 (8) and PSU 3 (4) are in progress. The most recent case to appear was in (99), which proves that no maximal subgroup of the Monster has socle PSU 3 (8).…”
Section: Sporadic Groupsmentioning
confidence: 99%
“…In (13), Breuer, Guralnick and Kantor conjectured that the converse is also true, and in dramatic recent progress, this conjecture (and much more) has been proved by Burness, Guralnick and Harper. See their paper (16) for an excellent description of some of the history of the problem, and the key results which go into the proof. It is conjectured that there is another equivalent condition to the one above for |G| ≥ 4: the graph Γ(G) contains a Hamiltonian cycle.…”
Section: Generation and The Generating Graphmentioning
confidence: 99%
“…3 and Burness, Guralnick, and Harper [4] completed the theorem by proving an influential conjecture of Breuer, Guralnick, and Kantor [3] regarding the case with d(G) 2.…”
Section: Introductionmentioning
confidence: 99%